Penerapan Inovasi Bahan Baku Alternatif untuk Efisiensi Biaya dan Keberlanjutan Produk Kerajinan - Sufitrayati, Sufitrayati; Fitriliana, Fitriliana; Ulfia, Ulfia; Syamsuddin, Nurfiani; Nurhadi, Alfian (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The strategic implementation of alternative raw materials has emerged as a pivotal approach to enhance cost efficiency and sustainability within the craft industry. This study employs a literature review approach to examine the use of local materials, organic waste, and recycled materials as substitutes for conventional inputs in MSME production. The findings indicate that replacing traditional raw materials can reduce production costs by up to 50% while enhancing product competitiveness in environmentally friendly markets. This innovation also generates social impact through the empowerment of local communities and the establishment of shorter supply chains. Nevertheless, challenges such as supply instability, technical limitations, and a paucity of regulatory support persist as significant obstacles. Consequently, a collaborative effort among government entities, micro, small, and medium-sized enterprises (MSMEs), designers, and research institutions is imperative to fortify the sustainable innovation ecosystem. The study's findings indicate that the adoption of alternative material innovations is not only conducive to economic efficiency but also serves as a catalyst for more inclusive and environmentally sustainable development.